The effects of financial literacy, materialism, and risk perception on millenials’ indebtedness - Ningrum, Ruziqa Hassana; Gantino, Rilla (Jurnal Ekonomi dan Bisnis, 2025)
Better financial literacy enables individuals, especially millennials, to make sound financial decisions. However, financial decisions, including indebtedness, are also influenced by other factors, such as materialism and risk perception. Accordingly, this study aims to investigate the effects of financial literacy, materialism, and risk perception on indebtedness among the millennial generation, employing a quantitative approach. We generated our data by distributing the questionnaires to the 190 respondents. The sample was selected using a purposive sampling technique to include individuals who were indebted and born between 1980 and 2000. This study ran SEM by using SmartPLS 4.0 to analyze the data. The empirical results reveal that financial literacy and risk perception negatively affect indebtedness, while materialism positively affects indebtedness. Our findings suggest that poorer financial literacy may lead to inadequate financial planning, while excessively materialistic individuals tend to be less appreciative of their possessions. Lastly, a lower risk perception leads to a poor understanding of the value of money. Our study suggests that financial literacy likely enhances the financial awareness, skills, attitudes, and behaviors essential for individuals’ future financial well-being. Such awareness helps them avoid impulsive behaviors and consider the risks associated with their financial decisions.